Emerging role of extracellular vesicles in mediating cancer cachexia. (19th October 2018) - Chitti, Sai V.; Fonseka, Pamali; Mathivanan, Suresh
Abstract : Cancer cachexia is a multifactorial metabolic syndrome characterized by the rapid loss of skeletal muscle mass with or without the loss of fat mass. Nearly 50–80% of all cancer patients' experience rapid weight loss results in ∼20% of cancer-related deaths. The levels of pro-inflammatory and pro-cachectic factors were significantly up-regulated in cachexia patients when compared with the patients who were without cachexia. It is becoming evident that these factors work synergistically to induce cancer cachexia. Extracellular vesicles (EVs) including exosomes and microvesicles are implicated in cell–cell communication, immune response, tissue repair, epigenetic regulation, and in various diseases including cancer. It has been reported that these EVs regulate cancer progression, metastasis, organotropism and chemoresistance. In recent times, the role of EVs in regulating cancer cachexia is beginning to unravel. The aim of this mini article is to review the recent knowledge gained in the field of EVs and cancer cachexia. Specifically, the role of tumour cell-derived EVs in promoting catabolism in distally located skeletal muscles and adipose tissue will be discussed.